Planning of time management on goal setting. an application for managers in different sectors - Doğruöz, İrem (My University, 2008)
Bu tezin amacı zaman yönetimi planlamasının hedef koyma üzerindeki katkısına bakmayı içermektedir. İlk bölümde, zaman yönetiminin kişisel ve organizasyonel olarak ayırt edici yönlerine değinmiştir. Bu bölümde, zaman yönetimi kavramı içinde kısa dönem ve uzun dönem planlama ile birlikte esneklik kavramının da üzerinde durulmuştur. Her ne kadar zaman yönetimi planlaması kişisel ve organizasyonel başarı için gerekli de olsa esnek olmayan bir uygulamada bazı problemler olabilir. Tezin ikinci kısmında, hedef koyma ve hedef koymanın yönetim literatürü içindeki yerine bakıldı. Başarılı bir hedef koymada planların yapılmasını ve kişisel öğelerin denetlenmesini içerir. Bu süreç aynı zamanda güçlü bir hedef bağlılığı ve

yeterliliği de içermektedir. Bunlar koyulan hedeflere ulaşmayı kolaylaştırır. Üçüncü bölüm bu önemli yönetim yaklaşımlarını ve ilişkilendirilen modelin kurulumu bir araya getirmektedir. Bu amaçla zaman yönetiminin, hedef bağlılığına ve öz yeterliliğe katkısı araştırılmıştır. Oluşturduğum bu model zaman yönetiminin hedef koyma üzerindeki katkısını incelemiştir. Modelim, kısa ve uzun dönem zaman yönetimi, esneklik ve hedef belirleme arasında pozitif bir ilişki olduğunu savunuyor. Buna ek olarak, zaman yönetiminin bu üç boyutunun hedef koyma üzerindeki etkililiğini, hedef bağlılığı ve öz yeterlilikle direk olarak etkileyeceğini de savunuyor. Son kısım ortaya atılan bu savların deneysel olarak test edilmesini içeriyor. Anket uygulaması, farklı sektörlerde çalışan, ağırlıklı olarak orta kademe yöneticilerine yapılmıştır. Araştırmamın sonuçları, kısa ve uzun soluklu planlama, esneklik ve hedef bağlılığı arasında kuvvetli bir ilişki olduğunu söylüyor. Literatüre bakıldığı zaman bu ilişkiyi inceleyen bir başka çalışma daha olmamış, bu yüzden direk bir kıyaslama pek mümkün olmamaktadır. Bununla birlikte uzun dönem planlamanın ve esnekliğin kişinin öz yeterliliğine bir katkısı olduğu bulunmuştur. Çalışmamda kısa ve uzun dönem planlamanın bunun yanısıra esnek olmanın, hedef koyma üzerinde pozitif bir katkısının olduğu görülmüştür. Anahtar Sözcükler: Zaman yönetimi planlaması ve hedef koyma Abstract The dissertation aims to provide an understanding of the contribution of time management planning on goal setting. In the earlier parts of the thesis, I have looked into more detailed accounts of time management planning and goal setting in time management. First chapter delves into the time management literature by distinguishing between the individual and organizational time management. Management strategies in time generally involve planning and scheduling. This is done in order to increase the effectiveness and the efficiency of either personal or corporate time or both. Within this chapter short-term planning, long-term planning and flexibility dimensions are studied in time management. Time management can be also seen as implementing the classical managerial methods to time. According to these theories, there should be flexibility in decision making process in order to cope with the ever-changing external and internal factors. Although, time management is essential for organizational and individual success there are several problems with very rigid time management. Rigid time management and planning could end up limiting the flexibility in the system and hence not allowing the individuals or organizations to alternate their methods when unexpected events take place. In the second section of the thesis, I analyzed the goal setting and how it has been discussed in the management literature. Simply, goal setting can be seen as deciding on specific goals and prioritizing them. To achieve these goals, plans should be designed and individual items should be checked. A successful goal setting would in the end also contain a form of evaluation to see if the goals that have been decided on are managed. Also this process includes a strong goal commitment and self-efficacy. This makes easier to reach the goals. The third section brings together these important aspects of management and establishes a relational model between them. For this purpose the contribution of time management have been studied on goal commitment and self-efficacy one by one. The relational model that I have developed looks into the contribution of time management on goal setting. My relational model claims that there will be strong positive relationship between short run and long run time management, flexibility and goal setting with goal commitment and self-efficacy. Additionally, according to my model’s expectations, the three dimensions of time management will influence goal setting effectiveness in a direct manner. The final part of the thesis tests the above stated propositions empirically. My empirical results give us a strong relationship between time management both in the short and long run, flexibility and goal setting. The first test is between time management dimensions and goal commitment. The results show us, planning of time management has a contribution on goal commitment. Each factor shows a significancy. The second test is between again the three time management dimensions and self-efficacy. Within this analyze we see that long-term planning and flexibility have a significant value besides short-term planning factor does not have a significant value. In the research whichs quesstionnaire is applied on mostly middle level managers at different sectors found that, both short term planning, long term planning and flexibility positively affect goal setting and increase the possibility of goal setting in an organization. Overall, the study concludes that there is a contribution of time management planning on goal setting. Key Words: Planning of Time Management and Goal Setting
Keywords: Planlama; Yönetim ve Organizasyon; Zaman Yönetimi